Answer:
x = 1 ⇔ y = -2.4
x = 2 ⇔ y = -1.8
x = 3 ⇔ y = -1.2
x = 4 ⇔ y = -0.6
Step-by-step explanation:
[tex]3x-5y=15[/tex]
→ Rearrange to make y the subject
[tex]-5y=-3x+15[/tex]
→ Multiply everything by -1
[tex]5y=3x-15[/tex]
→ Divide everything by 5
[tex]y=0.6x-3[/tex]
⇒ Substitute x = 1, 2, 3 and 4
[tex]y=0.6x-3\\ y=(0.6*1)-3\\ y=0.6-3\\ y=-2.4\\(1,-2.4)[/tex]
[tex]y=0.6x-3\\ y=(0.6*2)-3\\ y=1.2-3\\ y=-1.8\\(2,-1.8)[/tex]
[tex]y=0.6x-3\\ y=(0.6*3)-3\\ y=1.8-3\\ y=-1.2\\(3,-1.2)[/tex]
[tex]y=0.6x-3\\ y=(0.6*4)-3\\ y=2.4-3\\ y=-0.6\\(4,-0.6)[/tex]